Cell Adhesion: Stem‐Cell Clinging by a Thread: AFM Measure of Polymer‐Brush Lateral Deformation (Adv. Mater. Interfaces 3/2016). Issue 3 (5th February 2016) - Gunnewiek, Michel Klein; Ramakrishna, Shivaprakash N.; di Luca, Andrea; Vancso, G. Julius; Moroni, Lorenzo; Benetti, Edmondo M.
Abstract : In article number 1500456, E. M. Benetti and co‐workers measure the lateral deformability of polymer brushes. The behavior of surface‐interacting stem cells responds to the tendency of the brush to be laterally deformed. The formation of focal contacts is monitored, illustrated by hand drawings and imaged through an immunofluorescence micrograph. The density and morphology of these cell‐anchoring complexes are dependent on the brush frictional parameters, suggesting that the strength of cell attachment can be tuned.